Estudo da flora microbiana em colméia de Melipona scutellaris Latreille, 1811 - Ramos, Marina Abadia (1997)
The objective of this work was to contribute with data for the genetic ecology of uruçu (Melipona scutellaris, Latreille, 1811.) that is peculiar of north - east from Brazil. We evaluated the quantity of the microflora of different compounds of beehive of Melipona scutellaris. That are bees without sting. The quantities cultures were done in Tripticase Soya Agar (TSA) and MacConkey agar to honey, pollen, propoli and cavity food, this later was collected on higher, intermedium and lower portions of the cavity breed. The bees colonies were described by them nature caracteristics and the isolated representatives, and identified by biochemical tests. The microorganisms identified were gram positives staffs, gram positives coccus, fungus and enteric gram negatives Bacillus. The levei of contamination was different in the several investigated materiais, being higher on propoli (5,3 x 106 ufc/mL) and honey (3,5 x 104 ufc/mL). The morphology was the same in all colonies. The identified species between the isolated and your percentages are: Bacillus laterosporus (35,38%), Bacillus firmus (12,30%), Bacillus circulans (10,76%), Bacillus licheniformis (9,23%), xiBacillus brevis (6,15%), Bacillus subtilis (6,15%), Bacillus anthracis (4,61%), bacillus macerans (4,61%), Bacillus coagulans (3,07%), Bacillus megaterium (3,07%), Bacillus steathermophilus (3,07%), Bacillus sphaerícus (1,53%). Between the identified Bacillus five species are included Bacillus circulans, Bacillus licheniformis, Bacillus macerans, Bacillus sphaerícus e Bacillus subtilis, that could be associate on diseases in patient with predisposition and food intoxication, furthermore we found Bacillus anthracis that is the, Antrax agent (BRAUDE et al., 1981; WILLIAN, 1981; LUND, 1990; MANDELL et al., 1995). The results put forward the propoli and honey how the materiais with more significant amount (more than 104 ufc/mL) of bacteries. The isolated of Bacillus subtilis correspond to 11% (5,8 x 10'5 ufc/mL) in the propoli.